Analysis and Evaluation of Ghazali's Critiques in Tahafut Al-Falasafah to Ibn Sina in The Context of Theology - Syukur, Muhammad; Rezapour, Mohammad (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
The theological and philosophical understanding of issues related to the divine has always been a complex and contentious debate. Ghazali's work, Tahafut Al-Falasafeh, faces significant challenges in these issues, isolating and excommunicating philosophers on three specific points and accusing them of heresy and innovation in seventeen other areas. However, criticisms of Ghazali by Ibn Rushd in Tahafut Al-Tahaft, coupled with fundamental differences between the philosophies of Ibn Sina and Ibn Rushd, necessitate an exploration and analysis of Ibn Sina's perspective to dispel pessimism within the Islamic community regarding his philosophy. This study employs a literature review methodology with a descriptive, analytical, and critical approach. The research focuses on theological issues such as the proof of God's existence, the creation of the universe, the eternity of the world, and the science of God in Ibn Sina's works. Through a detailed analysis of Ibn Sina's viewpoints, it becomes evident that Ghazali's theological anxieties might stem from misinterpretations of the core tenets of Ibn Sina's philosophy.Abstrak: Pemahaman teologis dan filosofis mengenai isu-isu ketuhanan selalu menjadi perdebatan kompleks. Kitab Tahaft Al-Falasafeh karya Ghazali menghadapi tantangan signifikan dalam isu-isu ini, mengucilkan dan mengkafirkan para filosof dalam tiga isu serta menuduh mereka sesat dan bid’ah dalam tujuh belas isu lainnya. Namun, kritik terhadap Ghazali oleh Ibnu Rusyd dalam Tahaft Al-Tahaft dan perbedaan mendasar antara filsafat Ibnu Sina dan filsafat Ibnu Rusyd menimbulkan kebutuhan untuk menjelaskan dan menganalisis pandangan Ibnu Sina, agar masyarakat Islam tidak merasa pesimis terhadap filsafatnya. Penelitian ini menggunakan metode studi pustaka dengan pendekatan deskriptif, analitis, dan kritis. Fokus penelitian ini adalah pada isu-isu teologis seperti pembuktian keberadaan Tuhan, penciptaan alam semesta, keabadian alam, dan ilmu Tuhan dalam karya Ibnu Sina. Dalam analisis mendalam pandangan Ibnu Sina, tampak bahwa kegelisahan teologis Ghazali mungkin disebabkan oleh kesalahpahaman terhadap esensi filsafat Ibnu Sina.